Pengaruh Kualitas Pelayanan Dan Harga Tiket Terhadap Kepuasan Penumpang Di Stasiun Lebak Bulus Grab Pada Masa Pandemi Covid-19 - Soekarsono, Rame; Akbar, Reanaldi (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
The phenomenon behind this research is passenger dissatisfaction with the quality of MRT services at the Lebak Bulus Grab Station. In addition, the author was also interested in examining the effect of higher ticket prices than other transportation such as KRL and Transjakarta on passenger satisfaction. This research was conducted during the Covid-19 pandemic, a period that led to a decline in the number of passengers.The research method used by the researcher was a quantitative method. Data was collected through library and additional document research, field studies/surveys, and questionnaire distribution. The research sample included 100 passengers. Data analysis was conducted using questionnaire validity test, classical assumption test, hypothesis testing and multiple linear regression analysis.The results showed that service quality had a positive and significant effect on passenger satisfaction at the Lebak Bulus Grab Station during the Covid-19 pandemic, as evidenced by a significance value of 0.00 < 0.05, a t value of 7,247 > t table 1,985, and a regression coefficient of 0.399. The coefficient of determination (R2) value of 0.552 or 55.2% indicates that the Service Quality variable (X1) affected the Passenger Satisfaction variable (Y) by 55.2%, with the remaining 44.8% being the influence of other variables outside the study. Ticket prices had a positive and significant effect on passenger satisfaction at Lebak Bulus Grab Station during the Covid-19 pandemic, as evidenced by a significance value of 0.00 < 0.05, a t value of 5.927 > t table 1.985, and a regression coefficient of 1.069. The coefficient of determination (R2) value of 0.493 or 49.3% indicates that the Ticket Price variable (X2) affected the Passenger Satisfaction variable (Y) by 49.3%, with the remaining 50.7% being the influence of other variables outside the study. Simultaneously the quality of service and ticket prices have a positive and significant effect on passenger satisfaction at the Lebak Bulus Grab Station during the Covid-19 pandemic, as evidenced by a significance value of 0.00 < 0.05. The coefficient of determination (R2) value of 0.671 or 67.1% indicates that the independent variables Service Quality (X1) and Ticket Prices (X2) affected the dependent variable Passenger Satisfaction (Y) by 67.1%, with the remaining 32.9% being the influence of other variables not included in this research model.